Design Considerations of Capacitive Power Transfer Systems - Hussein Mahdi; Reiji Hattori; Bjarte Hoff; Anyu Uezu; Katsumi Akiyoshi (IEEE Access, 2023)
Capacitive power transfer (CPT) is a near-field wireless power transfer (WPT) technology that has attracted attention in different charging applications. By utilizing electric fields, CPT gives charging systems advantages in terms of cost, weight, flexibility, and mobility. This paper surveys a number of empirical published works in a period between 2015 and 2023. Additionally, it discusses theoretical and practical design considerations of a CPT system to understand and improve the technology and its applications. The paper studies the one- and two-port measuring approaches using vector network analyzers to determine the coupling parameters and compares the measurements to the simulated values using COMSOL Multiphysics ©. The two-port approach gives more accurate results than the one-port approach. The paper designs and tests a $\mathrm {13.56 \text {M} \text {Hz} }$ CPT system using the two-port measurement results. The system transfers $\mathrm {100 \text {W}}$ at 87.4% efficiency and $30 mm $ separation distance. Lastly, the paper discusses the design limitations and challenges of the CPT systems, aiming to emphasize the design obstacles that can drive the advancement of the CPT systems for wireless charging applications.